N-(5-Ethoxy-1,3,4-thiadiazol-2-yl)benzamide - Sung Kwon Kang (Acta Crystallographica Section E, 2012)
In the title compound, C11H11N3O2S, the dihedral angle between the thiadiazole and phenyl rings is 28.08 (7)°. In the crystal, molecules are linked into an inversion dimer by a pair of intermolecular N—H...N hydrogen bonds with an R22(8) graph-set motif.